The UV spectroscopic and chromatographic methods of hydroalcoholic extracts of aloe vera / Razuan Hilmi Md Sulji... [ et al.] - Md Sulji, Razuan Hilmi; J. Jalani, Kathleen; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Aloe vera which is also known as Aloe barbadensis Miller,is a plant that is commonly used for medicinal purposes and as treatments for various health issues. It produces two substances; gel and latex, which are used for commercial household products, halal food and cosmetics. Aloe gel is the clear, jelly-like substance found in the inner part of the Aloe leaf while Aloe’s yellow latex comes from the peel. Aloe vera is able to provide therapeutic effects such as wound healing, anti-inflammatory, antioxidant, laxative and antimicrobial properties. The objective of this study was to investigate the extracts via spectrophotometry (λ = 200 – 400 nm) and liquid chromatography. After 21 days, the ultraviolet spectra showed the evidence of the water molecules interactions and the hydroxyl groups in hydroalcoholic extracts. Significant peaks were also observed in the chromatograms. Further studies evaluating the stability of A. vera extracts should be carried out.